Performance Differences Between High and Low Empathy Ability in Conflicts of Interest: An ERP Study - Zhang N; Sun X (Psychology Research and Behavior Management, 2022)
Ni Zhang,1,2 Xuechuan Sun3 1Faculty of Psychology, Tianjin Normal University, Tianjin, People’s Republic of China; 2Mental Health Education Center for College Students, Weifang Medical University, Weifang, People’s Republic of China; 3Department of Information Engineering, Tianjin University of Commerce, Tianjin, People’s Republic of ChinaCorrespondence: Xuechuan Sun; Ni Zhang, Email sunxuechuan@tjcu.edu.cn; zhangni1223@126.comObjective: Empathy is negatively correlated with high levels of conflict behaviors, such as aggression. The purpose of this study was to examine whether there were still differences in the performance of high and low empathy ability under the general level of conflict.Methods: The Chinese version of the Interpersonal Reactivity Index (IRI-C) was distributed to 250 undergraduate students. The subjects were classified as the high-empathy group (n = 38) and the low-empathy group (n = 37). An improved ultimatum paradigm was used to create a relatively realistic general-intensity conflict situation. A total of 29 undergraduate students (15 in the low-empathy group) were subjected to conflicting or non-conflicting proposals. Event-related potential technology was used to record the EEG of the high- and low-empathy groups during the processing of different proposal types.Results: The high-empathy group had longer response times and lower rejection rates under different proposal types compared to the low-empathy group. The low-empathy group evoked more negative MFN amplitude under conflicting proposals than under non-conflicting proposals, while the difference was not significant in the high-empathy group. The low-empathy group induced greater LPP under non-conflicting proposals than under conflicting proposals, while the difference was not significant in the high-empathy group.Conclusion: High-empathy individuals showed more altruistic behaviors, and fewer conflict tendencies compared to low-empathy individuals. Low-empathy individuals had greater negative evaluations of conflicting offers, while high-empathy individuals weakened their negative evaluations of conflicting proposals because of their relatively high empathy. Compared to high-empathy individuals, low-empathy individuals showed stronger motivation to converge on non-conflicting proposals.Keywords: empathy, conflict of interest, altruism, MFN, LPP